Understanding the Determinants of E-wallet Continuance Usage Among Millennials in Klang - Ahmad, Kamilah; Zulkefley, Nur Amirah Adilah (Research in Management of Technology and Business, 2025)
Digital wallets have gained widespread popularity as financial transaction tools, primarily due to their innovative features that enhance user convenience. This study aims to assess millennials' satisfaction levels and their continued usage of e-wallets, by applying the Technology Continuance Theory. The data were collected using a questionnaire survey among consumers in Klang. The findings reveal a significant and positive relationship between user satisfaction and continued usage of e-wallets. Additionally, all selected determinants of satisfaction and continuance usage were found to be significantly related, supporting all hypotheses proposed in the study. These insights contribute to the current understanding of e-wallet adoption and provide valuable guidance for e-wallet developers seeking to improve their services to better meet users’ expectations.